(untitled) (Indian Journal of Experimental Biology (IJEB), 2022)
Lectins are diverse proteins that bind to carbohydrates and are involved in many important physiological processes. They are highly specific to the sugar molecules they bind and therefore, have many therapeutic and diagnostic applications. There are several lectins that display antiviral, antibacterial antifungal and antitumour activities. Characterization of new lectins paves way for comprehension of their diverse biological roles and mechanism of action, thus aiding in further exploration of lectins in various domains of biology. Here, we endeavoured to purify and characterize lectin from the seed of the legume,Pongamia. Pongamia pinnata (L.) Pierre (syn. Millettia pinnata), seed lectin (PPSL) was purified conventionally by ammonium-sulfate precipitation followed by size exclusion chromatography. The further lectin was physicochemically characterized by CD, fluorescence spectroscopy, mass spectroscopy and isothermal calorimetry. Hemagglutination studies with various mono and disaccharides showed specificity towards galactose. This specificity was reaffirmed by isothermal studies with appreciable thermodynamic parameters. Lectins have tremendous diagnostic applications. They are used as second-generation drug delivery systems.